(untitled) (Journal of Bio-Science, 2011)
Context: Plant based antimicrobial represent a vast untapped source for medicines and further exploration of plant antimicrobial neeto occur. Evolvulus alsinoides (L) (Convolvulaceae) is a perennial herb is used in traditional medicine in East Asia, India, Africa and Philippines to cure fever, cough, cold, venereal diseases, azoospermia, adenitis and dementia. Objective: The objective of this research was to evaluate the antimicrobial activity of the extracts of E. alsinoides on some clinical microbial isolates. Materials and Methods: The ed thanolic and aqueous extracts of the whole plant (leaves and twigs) were analysed for alkanoids, tannins, glycosides, steroids, flavonoids, saponins, volatile oil and resins. The determination of antibacterial activity was done using the agar well diffusion technique. Pure cultures of pathogenic bacteria such as Bacillus cereus, Staphylococcus aureus, Micrococcus leutus, Klebsiella Pneumoniae, Pseudomonas aeruginosa, Escherichia coli and Salmonella typhi were used for antibacterial activity assay, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Results: The ethanolic extract of the plant had MIC values ranging from 16 mg/ml to 512.5 mg/ml. The least MIC was 16mg-ml against Salmonella typhi while Bacillus cereus and Staphylococcus aureus showed the highest MIC of 512.5 mg-ml. In the aqueous extract the MIC ranged between 512.5 to >1025 mg/ml. Salmonella typhi, Micrococcus luteus and Staphylococcus aureus were not inhibited by the water extract. Phytochemical result showed ethanol to be a better solvent for the extraction of the bioactive agents in this plant which include: glycosides, alkaloids, saponins, tannins, flavonoids and volatile oil. Conclusion: In this study the gram-negative organisms had the lowest MICs and MBCs. This suggests their higher susceptibility to the extract of this plant. On the basis of the result obtained in this investigation it can be concluded that ethanol extract of Evolvulus alsinoides had significant in vitro broad spectrum antimicrobial activity. Keywords: Evolvulus alsinoides; Phytochemical screening; Antibacterial activity. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8769 JBS 2010; 18(0): 16-20